2011
DOI: 10.1007/s11886-011-0168-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Coronary Inflammation with FDG-PET: Feasibility and Clinical Hurdles

Abstract: Conventional algorithms and noninvasive imaging tests for the identification of stable, hemodynamically significant coronary artery disease offer little insight into the detection of potentially vulnerable and inflamed coronary plaques, those most likely to rupture and cause acute coronary syndromes. Positron emission tomography (PET) with fluorodeoxyglucose (FDG) serves as a potential novel modality for the identification of plaque inflammation, as initial studies in animal and human studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…A problem is the mismatch between CT and PET/SPECT images due to the fact that the heart is a moving object. In addition the observed coronary arteries are small [41]. The information contained in PET and MRI images is largely complementary, and their combination helps to predict plaque at high risk [42].…”
Section: Modality Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A problem is the mismatch between CT and PET/SPECT images due to the fact that the heart is a moving object. In addition the observed coronary arteries are small [41]. The information contained in PET and MRI images is largely complementary, and their combination helps to predict plaque at high risk [42].…”
Section: Modality Combinationsmentioning
confidence: 99%
“…It is stated by Wang et al [70], that the luminance of the surface of an object being observed is the product of the illumination and the reflectance, but the structure of the objects in the scene are independent of the illumination. The value of SSIM amounts between 0 and 1, where 0 represents zero correlation between the original image and 1 indicates the exact same image [41]. The SSIM is defined as [68,70]:…”
Section: Structural Similarity Image Measurementioning
confidence: 99%
“…High-risk plaques are positively (or outwardly) remodeled and contain a large lipid-rich necrotic core covered by an attenuated (thinned) and inflamed fibrous cap. 13 Numerous imaging [14][15][16][17][18][19][20][21][22] and postmortem studies [23][24][25][26][27] have established that most MI and acute events are caused by plaques with vulnerable features, especially when they expand in size and become luminally occlusive. 1,26 On this basis 2 ongoing prospective studies, PROSPECT II/ PROSPECT ABSORB (Providing Regional Observations to Study Predictors of Events in the Coronary Tree; ClinicalTrials.…”
mentioning
confidence: 99%
“…Although difficult, inflammation has been identified by intravascular demonstration of thermal heterogeneity and targeting of macrophages by positron emission tomography. [2][3][4][5][6][7][8][9][10][11][12][13] Studies over the past 2 decades have demonstrated that high-risk plaques are usually responsible for most acute coronary syndromes (ACS).…”
mentioning
confidence: 99%
“…Although difficult, inflammation has been identified by intravascular demonstration of thermal heterogeneity and targeting of macrophages by positron emission tomography. [2][3][4][5][6][7][8][9][10][11][12][13] Studies over the past 2 decades have demonstrated that high-risk plaques are usually responsible for most acute coronary syndromes (ACS). 1,[14][15][16][17] However, despite extensive interest and excitement regarding the potential of identifying high-risk lesions, plaque characteristics that have been shown to be associated with high-risk plaques have demonstrated a poor positive predictive value for identifying future events.…”
mentioning
confidence: 99%